PENDIDIKAN GENDER PADA ANAK USIA DINI - Hadianti, Asti Nur (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
Basically every parent wants their children to grow and develop according to what is expected. If a boy, then usually the parents want a son who brave and mighty, so that when these boys want to play games such as cooking, cooking, playing dolls, playing jump rope and so his parents would be angry with a reason because these games are games intended for girls. Vice versa, girls forbidden to play football, play war, climbing trees and so on, with the reasons for these games can change the image of the meek daughter. This is a parenting mistakes that can lead to misunderstandings in children. Whereas all types of games that can help cultivate and develop the potential of intelligence that exist in every child.